Reducing the effect of the ball on bat performance measurements - Nathan, A. M.; Smith, L. V.; Faber, W. L. (Sports Technology, 2011)
A simple physical model is presented that relates the ball-bat coefficient of restitution e to the ball coefficient of restitution e0 and dynamic stiffness k0. The model is used to develop a technique to normalize e to values of e0 and k0 for a "standard ball". The efficacy of this normalization technique is demonstrated by comparison with experimental data. It is shown to be vastly superior to a widely used technique that is based on the physically unjustified assumption that the ratio e/e0, commonly referred to as the Bat Performance Factor or BPF, is independent of both e0 and k0. A residual, but much reduced, dependence of the normalized e on k0 is observed and is shown through finite element simulations to be due to a dependence of the bat stiffness on the ball stiffness.